Highly-porous Super-Growth carbon nanotube sheet cathode develops high-power Lithium-Air Batteries. (20th December 2021) - Nomura, Akihiro; Mizuki, Emiko; Ito, Kimihiko; Kubo, Yoshimi; Yamagishi, Tomoko; Uejima, Mitsugu
Abstract: Lithium-Air Battery (LAB) is expected to develop ultra-high energy density batteries, but the low rate performance and poor cycle life of present LAB cells hinder practical development. Here we report that a highly porous carbon nanotube (CNT) cathode dramatically enhances the rate capability of LAB. Single-walled CNTs (SWCNTs) with wavy patterns prepared from the Super-Growth (SG) method successfully provided CNT sheets with high porosity of up to 94%. The pore structure was characterized by two distinct pores in size, namely, highly extended mesoscale (approximately 5–200 nm) pores formed inside CNT bundles that provide large surface area for oxygen reduction reaction (ORR) and inter-bundle gaps in a micrometer scale that works for oxygen diffusion path. This porous CNT sheet cathode significantly increased the discharge rate of LAB cells, specifically enabling a high discharge current density of 3.0 mA/cm 2 securing practical cell capacity of 3.3 mAh/cm 2, which is comparable to the current LiB technology that provides ∼3 mAh/cm 2 cell capacity at ∼1C rate (∼3 mA/cm 2 ) discharge. Furthermore, this highly porous cathode was also effective for extending the cycle life of LAB cells. Such bimodal pore architecture of the CNT sheet cathode paves the new strategy for developing high-power energy-dense LAB. Graphical abstract: Image, graphical abstract